The instability of shear normal wave in elastic waveguide of weakly inhomogeneous material - Hunanyan, A. A. (National Academy of Sciences of Armenia)
The influence of a weak longitudinal inhomogeneity on normal shear waves under different mechanical boundary conditions is investigated. It is shown, that for clamped smooth surfaces of isotropic elastic layer, occurs asymmetric localization of wave energy near the mid-surface layer. On the other side, for mechanically free smooth surfaces, near-surface localization of wave energy appears near mechanically free surfaces of the waveguide, but more intense localization appears again near the mid-surface layer. In both cases, due to the influence of material inhomogeneity on the normal wave, some distortion of amplitude and phase functions occur due to the change of formation coefficients (of frequencies). In both cases of boundary conditions, the weak inhomogeneity of the material leads to presence of frequency zones of transmission or prohibition of the formed wave. It is shown, that it is possible internal resonance in some higher forms. Исследуется влияние продольной, слабой неоднородности упругого материала волновода на распространение нормальной сдвиговой волны при разных механических граничных условиях. Показывается, что при защемлённых гладких поверхностях изотропного упругого слоя возникает асимметричная локализация волновой энергии около срединной плоскости слоя. При механически свободных гладких поверхностях появляются приповерхностные локализации волновой энергии у механически свободных границ волновода, но более интенсивная локализация появляется опять около срединной плоскости слоя. В обоих случаях вследствие воздействия неоднородности материала на нормальную волну, появляются искажения амплитуды и фазовой функции, обусловленные приведёнными коэффициентами (частотами) формообразования. В обоих случаях граничных условий слабая неоднородность материала приводит к появлению частотных зон пропускания или запрещению формированной волны. Оказывается, что при высших формах колебаний возможно возникновение внутреннего резонанса. Հետազոտվում է ալիքատարի երկայնական, թույլ անհամասեռության ազեցությունը սահքի նորմալ ալիքի տարածման վրա,, տարբեր եզրային պայմանների դեպքում: Ցույց է տրվում, որ իզոտրոպ առաձգական շերտի ամրակցված հարթ եզրերի դեպքում, միջին մակերևույթի մոտ, առաջանում է ալիքային էներգիայի ասիմետրիկ տեղայնացում: Ալիքատարի մեխանիկորեն ազատ հարթ եզրերի դեպքում, առաջանում են ալիքային էներգիայի մերձմակերևութային տեղայնացումներ: Բայց ալիքային էներգիայի ավելի ինտենսիվ տեղայինացում, նորից տեղի է ունենում միջին մակերևույթի շուրջ: Երկու դեպքում էլ տարածվող ալիքի վրա նյութի անհամասեռության ազդեցության հետևանքով, բերված հաճախության (կամ ալիքի հարմոնիկայի) փոփոխության հետևանքով տեղի է ունենում ալիքի լայնույթի և/կամ փուլի խոտորում: Եզրային պայմանների երկու դեպքում էլ ալիքատարի նյութի թուլյ անհամասեռությունը բերում է հաճախությունների արգելանքի կամ թողարկման տիրույթների առաջացման: Պարզվում է, որ բարձր հաճախությունների դեպքում հնարավոր է ներքին ռեզոնանսի առաջացում:
Keywords: Mechanics of deformable solids; Waves